Borrowing size in networks of cities: City size, network connectivity and metropolitan functions in Europe*. (24th November 2015) - Meijers, Evert J.; Burger, Martijn J.; Hoogerbrugge, Marloes M.; Meijers, Evert; Burger, Martijn
Abstract: The current dynamics in the Western European urban system are in marked contrast with the bourgeoning literature stressing the importance of agglomeration for economic growth. This paper explores whether this is due to the rise of 'city network economies', leading to processes of borrowed size as well as the rise of agglomeration shadows in networks of cities. The spread of metropolitan functions over Western European cities is analysed. It is found that network connectivity positively enhances the presence of metropolitan functions, but local size remains the most significant determinant for most types of functions. The importance of size and network connectivity differs across metropolitan functions and across cities.